2017
DOI: 10.1177/1369433217717117
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis behavior of traditional timber structures by full-scale tests

Abstract: To study the seismic response of a traditional timber structure in China, a full-scale model capturing the main characteristics of a representative ancient Chinese wooden structure in Song Dynasty (960-1279 AD) was established and tested considering three different levels of vertical loads, which is one-story sophisticated timber structure consisting of four columns and Dou-gong sets. A swing column was used to apply the synchronous horizontal force. Tests under the low-cyclic loading were performed considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Several experimental tests have been carried out to investigate the behavior of full-scale structures using shaking tables (see e.g., Figure 7a) or sub-structures subjected to lateral loadings [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. At the component scale, for log houses and timber frame buildings, cyclic or monotonic tests have been performed on shear walls as the lateral load-bearing system, while in post and beam systems with beam-column connections that resist lateral loads, the connections are simulated as illustrated in Figure 7b,c.…”
Section: Seismic Vulnerability Assessmentmentioning
confidence: 99%
“…Several experimental tests have been carried out to investigate the behavior of full-scale structures using shaking tables (see e.g., Figure 7a) or sub-structures subjected to lateral loadings [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. At the component scale, for log houses and timber frame buildings, cyclic or monotonic tests have been performed on shear walls as the lateral load-bearing system, while in post and beam systems with beam-column connections that resist lateral loads, the connections are simulated as illustrated in Figure 7b,c.…”
Section: Seismic Vulnerability Assessmentmentioning
confidence: 99%
“…Research findings have revealed the unique role of the hysteresis curves in reflecting the seismic behaviour of wood frame [19][20][21]. Using the data acquired from the tests, the force-displacement (P-Δ) hysteresis curves for two wood frame models, one with a unilaterally and another with a circumferentially damaged column foot, were obtained as shown in Figures 9 and 10, respectively.…”
Section: Hysteresis Curvesmentioning
confidence: 99%
“…In order to study the stress mechanism and mechanical model of a straight tenon with wooden bolt pins, Hu et al [26] fabricated three sets of full-size models and conducted low-cycle repeated loading tests. In order to study the hysteretic property of ancient architectures, the research group of Chen et al [27] fabricated a full-size frame model of the wooden structure of Chinese Song Dynasty, conducted pseudo-static tests by exerting three vertical loads on the model, and proposed the limit of the angle of displacement for structure design and the equivalent viscous damping and ductility factor for the dynamic response analysis. Guan et al [28] built a 3D nonlinear fnite element model to simulate the contact stress of mortise-tenon joints under the wedge pressure of diferent sizes of woken corks and the strain on the column.…”
Section: Introductionmentioning
confidence: 99%